Proximal Humerus Fractures in the Geriatric Population Present an Opportunity to Improve Recognition and Treatment of Osteoporosis. (9th July 2020) - Piple, Amit; Smith, Christian Taylor; Barton, David W.; Carmouche, Jonathan J.
Introduction: Osteoporosis remains an undertreated disease entity causing substantial morbidity and mortality. Proximal humerus fractures are a common sentinel fracture, providing an opportunity to intervene with antiresorptive therapy before more subsequent fractures occur. Despite the success of programs aimed to improve postfracture osteoporosis recognition and management, less than 30% of patients presenting with a fragility fracture are diagnosed or treated for osteoporosis nationally. Further elucidation of diagnosis and management of osteoporosis following humerus fracture is warranted. Methods: This study is a retrospective cohort review intended to demonstrate the current state and clinical import of osteoporosis diagnosis and management following a humerus fracture at a large academic tertiary care center without an established secondary fracture prevention program. All patients 50 years of age or older who presented with a new humerus fracture between 2008 and 2014 were included. Outcome measures included: The initiation of antiresorptive therapy or screening before fracture, within the year following fracture, or not at all. Results: One thousand seven hundred unique geriatric patients were seen for humerus fractures. Nineteen percent of these patients (n = 324) were already on an antiresorptive medication. Three percent of previously untreated patients were started on antiresorptive therapy during the year after their fracture, with 31 or 2% of untreated patients starting at any subsequent point. Seventy-six percent of patients (n = 1301) were never prescribed antiresorptive therapy. Discussion and Conclusion: In the absence of a dedicated program to improve secondary fracture prevention following minimal trauma spinal fractures, recognition and treatment of osteoporosis in patients remained inadequate over time despite numerous calls to action on the topic in the orthopedic literature and public health initiatives. Undertreatment of osteoporosis puts patients at increased risk for additional fractures. This study underscores an opportunity to improve bone health by aggressively screening for and treating osteoporosis in geriatric humerus fracture patients.